Women in Unorganized Sector: Problems & Issues in India - Shyam, Mamta (Journal of Commerce and Trade, 2015)
Women make up 32 per cent of the informal economy, comprising 20 per cent of the agricultural and non-farm workforce. In India, 118 million women workers are employed in the unorganized sector, which is 97 per cent of the total female workers in India. Most of the women in the country are less educated than the men, thus working mainly as unskilled labor and thus getting low wages. They are considered physically inferior to men, so they are assumed to work less, thus being paid less. When Amartya Sen spoke about women’s welfare, he was accused in India of expressing foreign concerns. Indian women don’t see equality that way, he was told. But he argues that if they don’t think so, they should be given a chance to think so. Women’s economic participation can be referred to in the field of goods and service production in national income statistics. However, the job participation rate for women has been lower at 26 per cent compared to 52 per cent for men. The problem is that women work all the time.